ON THE QUESTION OF DIASTOLIC DYSFUNCTION OF THE LEFT VENTRICLE IN METABOLIC SYNDROME - Tashtemirova Irodaxon Makamboyevna (Scholar Express Journals, 2022)
In this article, an epidemic of metabolic diseases is currently approaching - obesity, diabetes mellitus (DM), arterial hypertension (AH). Analyzes have been reported that the proportion of the population with metabolic syndrome (MS) leading to the development of type 2 diabetes and cardiovascular disease (CVD) is growing faster. Predicting the progression of Metabolic Syndrome is determined not only by blood pressure (BP), glycemic control level, and metabolic disorders, but also by heart remodeling
Keywords: Metabolic Syndrome; direct correlation; systolic parameters; diastolic filling